A VIEW OF INTERAGENCY OPERATIONS IN SOUTH AMERICA IN THE FACE OF ILLEGAL MINING IN THE AMAZON: AN APPROACH FROM BRAZIL AND ECUADOR - Santillán, Rómulo Marcelo Borja (Seven Editora, 2025)
This study analyzes the dynamics of interagency cooperation in South America in the context of the fight against illegal mining in the Amazon region, with special emphasis on the cases of Brazil and Ecuador. It examines how the States of the Amazon basin articulate joint actions through inter-institutional cooperation and coordination agreements to mitigate the effects of this illicit activity on biodiversity and regional security. The research is structured in three axes: a theoretical-conceptual framework on interagency operations and the formulation of defense policies; an analysis of the sectors involved and the role of the Armed Forces in the Amazon; and a discussion of the results obtained along with possible solutions. Under a qualitative approach, supported by bibliographic review and documentary analysis, the work provides a comprehensive understanding of the mechanisms of regional governance in the face of a shared threat. DOI: https://doi.org/10.56238/sevened2025.018-039